Assessing The Psychometric Properties of The Internet Addiction Test (IAT) Among Indian School Students - Aarti Mishra; Priyamvada Shrivastava; Mahendra Kumar (Medsci Publications, 2023)
Background: Internet addiction is found to be a growing global problem and India is not exceptional. Adolescents are more over addicted to internet and suffering with mental confusions and deviation in behaviour. Several instruments have been developed for assessment of Internet addiction. Internet Addiction Test (IAT) is the most widely used tool to assess internet addiction, but psychometric properties of the IAT have not yet been examined in the Indian adolescence. The aim was to examine the validity and reliability of the 20-item Internet Addiction Test in Indian School Students. Methodology: Seven hundred fifty-two students from a CBSE school of Raipur, India was randomly selected in our study. The reliability and validity of IAT was examined. Confirmatory factor analysis was used to examine the structural validity of IAT. Results: It was found that the factor loading of the IAT varied between 0.40 and 0.82. Cronbach's alpha coefficient for the scale was found to be 905. The total correlations were calculated and had a value range from 0.406 to 0.659 for the 20 items. The psychometric properties indicate that the factor loading reveal that the test revolve around six factors (Salience, Excessive Use, Neglected Work, Anticipation, Lack of Control, and Neglected Social Life). The Cronbach's alpha is high for all the 6 components. IAT is a proper tool for evaluating internet addiction in Indian school students. Conclusions: The findings obtained in this study indicate that overall, IAT has adequate psychometric properties for the assessment of internet addiction in Indian school students.